Maleagi 1 vers 1 : eksegetiese en kanoniese studie - Oosthuizen, J. A. A.(Jan Antonie Alexanderf1931-) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (B.D.) -- Universiteit van Stellenbosch, 1957.